IMPLEMENTATION A WEB-BASED ONLINE LETTER APPLICATION AT MANTINGAN VILLAGE APPARATUS - Purwati; Indra Lina Putra; Muhammad Ali Subkhan; Sofia Ulfah; Triana Hasty Kusuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Technology that is increasingly developing in the modern era gives rise to various innovations provided by students, society and scientists with the aim of facilitating human life. The innovations that are present are expected to help human life in carrying out their daily lives. But unfortunately, innovations that facilitate human work are currently not so massive, especially in the field of population data. Manual data processing has been causing problems due to human error. Humans make a lot of mistakes in various circumstances. Data related to population administration, which is the process of submitting letters concerning population data in several areas, especially in Mantingan Village, is still carried out manually. In addition, when data is entered into the mail archive, the time required becomes longer and sometimes even lost and damaged during natural disasters such as landslides, earthquakes and floods. Residential document files that are manual in nature can be damaged and take a long time to re-register. The given problem initiated the author to propose a technology-based residence letter system. In this web-based online letter-making application, it is useful in supporting the making of residence documents with the main functionality, namely processing population administration applications more efficiently. The making of this web-based online mail program is the result of a collaboration between the Balekambang Jepara Polytechnic and the Mantingan Village Government, Tahunan District, District. Then this program became the theme proposed to participate in the Matching Fund program through the Kedaireka platform, namely the collaboration between the Balekambang Jepara Polytechnic and Dudi (Industrial World) namely Mitra, CV. Umbrella Corporation which batch 3 Matching Fund program in 2022.